The Effectiveness of Banana Stem, Pineapple Leaf and Sugarcane Peel as Bio-sorbent in Wastewater Treatment - SHAHWAN, NUR SYAZWANI; JALIL, DR. MAS RAHAYU (Progress in Engineering Application and Technology, 2023)
Banana stem, pineapple leaf and sugarcane peel are an agricultural waste whereas an abundance of worthless banana stem, pineapple leaf, and sugarcane peel can be considered a rise in trash. The purpose of this study was to look into the potential of banana stem, pineapple leaf, and sugarcane as bio-sorbents in palm oil mill effluent (POME) treatment, in order to address the growing amount of banana stem, pineapple leaf, and sugarcane peel as agricultural waste. In this research, the removal of turbidity and reduction of chemical oxygen demand (COD) from palm oil mill effluent (POME) was investigated and explored with the adsorption process performance research. From previous research, banana stem has the ability to adsorb heavy metal such as copper ion, zinc ion and iron ions which exist in palm oil mill effluent (POME).